Funds and funds flow identified for the purpose of preparing a funds statement for an accounting entity in terms of an appropriate objective - Elliott, G. J.(Graham John) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Comm.) -- University of Stellenbosch, 1982.